Lateritization process of peridotites in Siruka, Choiseul, Solomon Islands - Christopher V. Sagapoa; Akira Imai; Takeyuki Ogata; Kotaro Yonezu; Koichiro Watanabe (Journal of Applied Geology, 2015)
The lateritic weathering crusts exposed in Siruka, Choiseul Islands, Solomon Islands, were developed on the expense of serpentinized peridotite underlain by Siruka schists and Voza lavas with a subhorizontal contact. The lateritic profiles consist of three generalized zones: bedrock, saprolitic zone (weathered and decomposed zone) and the limonitic zones. The profiles demonstrate variations in depths and continuity but illustrate mineralogy and geochemical affinity down profile and are analogous to saprolitic nickel laterite deposits. Silica and magnesia in the bed rock and the saprolitic zones have been removed and only the residual elements (iron, chromium, aluminium, manganese, cobalt and nickel) remain in the limonitic zone. These elements are relatively concentrated as a result of the removal of the soluble elements. Nickel is associated with silica and magnesia, as lizardite ormixed gels (garnierite nickel ore) at the weathering fronts. On the other hand, nickel, with generally low concentrations (